2004
DOI: 10.1590/s1516-35982004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das equações de predição das exigências de proteína para matrizes pesadas na fase de crescimento

Abstract: RESUMO -Objetivou-se avaliar as equações para predição das exigências protéicas de matrizes pesadas em crescimento, desenvolvidas em estudos anteriores na Faculdade de Ciências Agrárias e Veterinárias da UNESP, Jaboticabal, tendo como padrão de comparação as recomendações estabelecidas pelo manual de criação da linhagem. Foram utilizadas 288 matrizes pesadas da linhagem Hubbard Hy-Yield, com cinco semanas de idade, em delineamento inteiramente casualizado, com dois tratamentos e seis repetições, sendo 24 aves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 10 publications
1
12
2
2
Order By: Relevance
“…Ao contrário do obtido no presente trabalho, Silva-Filardi et al (2000) não observaram alteração no teor de proteína na carcaça de matrizes pesadas em crescimento ao longo da 3ª a 20ª semana de idade, sendo, em média, de 16%. Este valor é menor que o encontrado para as codornas (Tabela 3).…”
Section: Desempenho Das Aves E Composição Corporalunclassified
See 1 more Smart Citation
“…Ao contrário do obtido no presente trabalho, Silva-Filardi et al (2000) não observaram alteração no teor de proteína na carcaça de matrizes pesadas em crescimento ao longo da 3ª a 20ª semana de idade, sendo, em média, de 16%. Este valor é menor que o encontrado para as codornas (Tabela 3).…”
Section: Desempenho Das Aves E Composição Corporalunclassified
“…No entanto, esteve próxima à observada pelos mesmos autores para frangas Lohmann, de 762 mg de N/kg 0,75 /dia, utilizando a técnica do abate comparativo. Silva-Filardi et al (2000), empregando a metodologia do abate comparativo, também estimaram as exigências de mantença para matrizes pesadas de 3 a 20 semanas de idade em 3,75 g de PB ou 600 mg de N/kg 0,75 /dia, sendo pouco inferior à obtida com codornas nesta fase.…”
Section: Exigências De Mantençaunclassified
“…Silva et al (2010) found estimates for European quails different from the requirement obtained by Silva et al (2004b) with Japanese quails from 15 to 32 days of age (4.86 versus 4.75 g/kg 0.75 /day) housed in the floor. Filardi et al (2000), working with growing breeding pullets, determined different estimate values for protein maintenance between the comparative slaughter methodology and the technique of nitrogen balance (3.75 vs. 2.02 g/kg 0.75 /day), indicating differences in the experimental methodology.…”
Section: Resultsmentioning
confidence: 99%
“…However, another important factor that changes the nutritional needs is the methodologies used [18,[25][26][27][28][29][30][31], such as the CS and NB techniques used in the elaboration of prediction equations.…”
Section: Crude Protein: Methodologies and Requirementmentioning
confidence: 99%
“…The CP (g/bird/day) requirements for maintenance were predicted by the CS technique, with growing animals, in the studies [26,29,30], which, respectively, used: pullets (42-63 days of age), heavy matrices (3-20 weeks of age) and Japanese quails (15-32 days of age). The values are similar between the species, 4.765 and 4.752 × body weight 0.75 for pullets and quails; however, they are discrepant when compared to heavy matrices 3.77 × body weight 0.75 .…”
Section: Crude Protein: Methodologies and Requirementmentioning
confidence: 99%